Seasonal variation in the morphokinetics of in-vitro-derived bovine embryos is associated with the blastocyst developmental competence and gene expression - Yaacobi-Artzi, Shira; Kalo, Dorit; Roth, Zvi (Frontiers in Reproductive Health, 2022)
Summer heat stress is a major cause of reduced development of preimplantation embryos. Nevertheless, seasonal effects on embryo morphokinetics have been less studied. We used a non-invasive time-lapse system that allows continuous monitoring of embryos to study the seasonal impact on embryo morphokinetics. The experiments were performed during the cold and the hot seasons. Cumulus-oocyte complexes were aspirated from ovaries, in-vitro-matured, and fertilized. Putative zygotes were cultured in an incubator equipped with a time-lapse system. The cleavage and blastocyst formation rates were lower in the hot vs. the cold season (p < 0.01). The kinetics of the embryos differed between seasons, reflected by a delay in the second cleavage in the hot vs. the cold season (p < 0.03). The distribution of the embryos into different morphological grades (good, fair, and poor) throughout the first three cleavages differed between seasons, with a higher proportion of good-grade embryos in the hot season (p < 0.03). Cleaved embryos were categorized as either normal or abnormal, based on their first cleavage pattern. Normal cleavage was defined as when the first cleavage resulted in two equal blastomeres and further classified as either synchronous or asynchronous, according to their subsequent cleavages. Abnormal cleavage was defined as when the embryo directly cleaved into more than two blastomeres, it cleaved unequally into two unevenly sized blastomeres, or when the fusion of already divided blastomeres occurred. The proportion of abnormally cleaved embryos was higher in the hot season vs. the cold one (p < 0.01), reflected by a higher proportion of unequally cleaved embryos (p < 0.02). In the cold season, abnormally cleaved embryos had a lower potential to develop into blastocysts relative to their normally cleaved counterparts (p < 0.001). Blastocysts that developed in the cold and the hot seasons differed in the expression of genes that related to the cell cycle (STAT1; p < 0.01), stress (HSF1; p < 0.03), and embryo development (ZP3; p < 0.05). A higher expression level was recorded for the STAT1 and UHRF1 genes in blastocysts that developed from unequally vs. the synchronously cleaved embryos (p < 0.04). We provide the first evidence for a seasonal effect on embryo morphokinetics, which might explain the reduced embryo development during the hot season.